I'll never tell - McKenzie, Catherine (Lake Union Publishing, 2019)
"What happened to Amanda Holmes? Twenty years ago, she was found bludgeoned in a rowboat at the MacAllister family's Camp Macaw. No one was ever charged with the crime. Now, after their parents' sudden deaths, the MacAllister siblings return to camp to read the will and decide what to do with the prime real estate the camp occupies. Ryan needs to sell. Margaux hasn't made up her mind. Mary believes in leaving well enough alone. Kate and Liddie--the twins--have opposing views. And Sean Booth, the grounds keeper, just hopes he still has a home when all is said and done. But it's more complicated than a simple vote. The will stipulates that until they unravel the mystery of what happened to Amanda, they can't settle the estate. Any one of them could have done it, and each one is holding a piece of the puzzle. Will they work together to finally discover the truth, or will their secrets finally tear the family apart?" --